Better quality potatoes for Uganda. Piloting seed potato production using rooted transplants of apical cuttings and assessment of ware potato storage. Project profile. - International Potato Center (International Potato Center, 2019)
Potato has underexploited potential to contribute to food security and income generation among Ugandan small-scale women and men farmers. This project focuses on building the skills of private sector early-generation seed producers and decentralized seed multipliers and improving current ware potato storage and marketing practices to ease the high seasonal market price fluctuations.